Visions of the Emerald City : Modernity, Tradition, and the Formation of Porfirian Oaxaca, Mexico - Overmyer-Velázquez, Mark (Book collections on Project MUSE., 2006)
This is an absorbing historical analysis of how Mexicans living in Oaxaca City experienced 'modernity' during the lengthy 'order and progress' dictatorship of Porfirio Díaz (1876-1911).